New mammal assemblage from last interglacial in Argentine Pampas: Debating biostratigraphic and biochronological reliability - Bellinzoni, Jonathan (2025)
This study analyzes one of the most complete mammalian fossil records from the Middle to the end of thePleistocene in the Pampean Region, recovered from the Salto de Piedra Paleontological Locality along Tapalqu´eCreek. The site preserves a fluvial-palustrine sequence with six depositional units (U1–U6), separated by erosiveunconformities or pedogenetic horizons. Radiometric dating (OSL and AMS 14C), integrated with sedimentologicaland faunal data, allows correlation with Marine Isotope Stages: Unit 1 (MIS 6–5; >127 ka), Unit 2 (MIS 3;~40.5 ka), Units 3–4 (MIS 2; 38–11.2 ka), and Units 5–6 (MIS 1; 12.6–7.8 ka). Three fossil assemblages wereidentified (U1, U3–4, U5–6), primarily linked to fluvial channels. The record provides critical biochronologicalinformation, with fossils showing minimal weathering and abrasion, and no evidence of reworking. Theoccurrence of Equus neogeus in U1 (>127 ka) expands the lower limit of its biozone back to ~300 ka. Index taxain Unit 1—Glyptodon munizi, Megatherium americanum, Equus neogeus—highlight biozone overlap, challenging thestratigraphic resolution of traditional schemes. Due to the lack of exclusive taxa and overlapping ages, wepropose merging the Bonaerean with the Lujanian Stage/Age (~300–11.6 ka). These findings call for a revisionof Quaternary biozone frameworks in South America and improve biostratigraphic resolution for the Pampeanfossil record.